Tunable lanthanum doping in double perovskite films for read-only memory. Issue 15 (1st August 2022) - Lyu, Chongguang; Qian, Yuchi; Zhan, Guixiang; Yuan, Jiaxiao; He, Kaiyue; Min, Huihua; Liu, Chang; Cao, Yang; Song, Xuefen; Ma, Huifang; Liu, Yunfei; Wang, Lin
Abstract: Rare earth ions have been widely investigated as active dopants in various materials because of their distinct optical, electronic and magnetic properties. Halide perovskite resistive memories have attracted increasingly recent interest for tremendous potential applications in computation and data storage techniques. However, it remains unexplored to implement rare earth doping strategy for tuning perovskite resistive memories. Here, we report read-only memories based on environment-friendly and air-stable lead-free double perovskite Cs2 AgBiBr6 films, which is particularly tuned by rare earth La 3+ doping. We use the vacuum sublimation and solution processing method to obtain Cs2 AgBiBr6 crystals doped by different content La 3+, and fabricate resistive memory devices based on doped Cs2 AgBiBr6 films. The simplest sandwich-like structure composed of ITO/La-doped-Cs2 AgBiBr6 /Ag only is designed in cross-bar array architecture with high-integration and simple operation. The resistive memory device of La-doped Cs2 AgBiBr6 films demonstrate a typical write-once-read-many-times (WORM) behavior with low onset voltage of 1 V and long retention time of 12000 s. In particular, the ON/OFF ratio of the La-doped Cs2 AgBiBr6 film is 100 times higher than that of the undoped Cs2 AgBiBr6 film. This study provides a new insight to design and manipulate memory devices based on lead-free halide perovskite materials through doping effect of rare earth ions.